Inflammatory Cytokines in Diabetic Nephropathy - Javier Donate-Correa; Ernesto Martín-Núñez; Mercedes Muros-de-Fuentes; Carmen Mora-Fernández; Juan F. Navarro-González (Journal of Diabetes Research, 2015)
Probably, the most paradigmatic example of diabetic complication is diabetic nephropathy, which is the largest single cause of end-stage renal disease and a medical catastrophe of worldwide dimensions. Metabolic and hemodynamic alterations have been considered as the classical factors involved in the development of renal injury in patients with diabetes mellitus. However, the exact pathogenic mechanisms and the molecular events of diabetic nephropathy remain incompletely understood. Nowadays, there are convincing data that relate the diabetes inflammatory component with the development of renal disease. This review is focused on the inflammatory processes that develop diabetic nephropathy and on the new therapeutic approaches with anti-inflammatory effects for the treatment of chronic kidney disease in the setting of diabetic nephropathy.